2015
DOI: 10.1016/j.tins.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms underlying learning and the inheritance of learned behaviors

Abstract: Gene expression and regulation is an important sculptor of the behavior of organisms. Epigenetic mechanisms regulate gene expression not by altering the genetic alphabet but rather by the addition of chemical modifications to proteins associated with the alphabet or of methyl marks to the alphabet itself. Being dynamic, epigenetic mechanisms of gene regulation serve as an important bridge between environmental stimuli and genotype. In this review, we outline epigenetic mechanisms by which gene expression is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 88 publications
(88 reference statements)
0
80
0
1
Order By: Relevance
“…Interestingly, in that study exposure effects were identified at specific sites in both exposed mothers and offspring, and mothers' methylation correlated with offspring methylation. It is also necessary to investigate multiple generations to differentiate among exposure effects, epigenetic inheritance and social transmission (9). Animal models can provide further mechanistic understanding of how extreme stress effects mediate changes in offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in that study exposure effects were identified at specific sites in both exposed mothers and offspring, and mothers' methylation correlated with offspring methylation. It is also necessary to investigate multiple generations to differentiate among exposure effects, epigenetic inheritance and social transmission (9). Animal models can provide further mechanistic understanding of how extreme stress effects mediate changes in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Biological alterations associated with PTSD, and/or other stressrelated disorders have also been observed in offspring of trauma survivors who do not themselves report trauma exposure or psychiatric disorder (3)(4)(5). Animal models have demonstrated that stress-exposure can result in epigenetic alterations in the next generation, and such mechanisms have been hypothesized to underpin vulnerability to symptoms in offspring of trauma survivors (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…These research observations are in the direction of an epigenetic explanation of inter -individual variation and long lasting effects but have to be verified in future research. (18)(19)(20) Yehudas' actual research approach (21) is very promising as it attempts to offer a global view on gene expression and gene methylation and to specify what differentiates people with PTSD and people without PTSD in order to "identify causal networks that can help diagnose PTSD and identify new treatment targets in the brain" (22).…”
Section: Resultsmentioning
confidence: 99%
“…1D). It is notable that a large proportion of examples of non-genetic inheritance reported so far in mammals relate to carbohydrate and lipid metabolism, and brain and behavior (Choi and Mango, 2014;Bale, 2015;Sharma, 2015b;Szyf, 2015;Dias et al, 2015). In addition, a recent study has found that thousands of genes that escape genome-wide DNA demethylation in human primordial germ cells (PGCs), whose complete data set is not reported, are over-represented in genes expressed in brain, and genes associated with metabolic, and neurological and neuropsychiatric disorders .…”
Section: Resultsmentioning
confidence: 99%